Pengendalian Internal Dalam Konteks Pengelolaan Pajak Reklame - Josua Rolamdo; Ni Putu Eka Widiastuti (Perspektif Akuntansi, 2021)
Internal control of local taxes is the key factor in the success of tax management, including the collection of advertisement taxes. Therefore, an adequate internal control analysis is essential in administering the advertisement tax. This study uses a qualitative method by taking objects in the Kelapa Gading area, North Jakarta. Data were collected through observation, interviews with four key informants, namely the Head of the Regional Revenue Service Unit (UPPD), Head of the Service Unit (Kasatpel Pelayanan), Head of Billing Unit (Kasatpel Penagihan), and the Data Administration Unit. This study indicates that the internal control of the advertisement tax in the Kelapa Gading, North Jakarta has been running effectively. The tax management information system plays significant role in internal control by providing information of tax arrears.